Prevalence, risk factors, efficacy of hoof trimming, and treatment protocols of lameness and hoof lesions in dairy cows in Malaysia - Babatunde, Sadiq Mohammed (2021)
Lameness is one of the most important health issues in dairy cows. This study aimed to (1) determine the prevalence of lameness and hoof lesions and their risk factors in Malaysian dairy herds, (2) evaluate the efficacy of hoof trimming (HT) techniques for lameness management in grazing and non-grazing cows, and the short-term impact on behavioural activities, cortisol levels, and milk yield, 3) to evaluate the impact of treatment protocols for hoof horn lesions on recovery rates, behaviour and milk yield, and 4) assess dairy farmers’ knowledge, attitude, and practices regarding lameness management. The first study comprised a study population of 1,051 lactating cows from 29 dairy farms in Selangor (n = 9), Perak (n = 9), Negeri Sembilan (n = 6) and Johor (n = 5). Lameness was assessed by locomotion scoring, followed by hoof examination and collection of farm and cow-level characteristics. The prevalence of lameness was 34.2% (95% Confidence Interval: 22.2-50.0%). Sole ulcers were the predominant lesion (24.9%), followed by white line disease (19.6%), sole haemorrhage (10.2%), and digital dermatitis (5.6%). Overall, these lesions were influenced by different factors at the cow and farm levels. Three studies were conducted for the second aspect that focused on preventive hoof trimming. First, 520 non-lame cows from two grazing and three non-grazing dairy farms were allocated to either hoof trimming (using the Dutch five-step method) or control groups. Second, 418 nonlame cows from one farm were randomly allocated into three groups: Dutch fivestep HT (TRIM1), modified HT method (TRIM2), and a control (CON) group. Locomotion scores and other cow characteristics were assessed monthly for one lactation in all the experimental groups. Third, 20 non-lame cows without hoof lesions were randomly allocated to trimmed (n = 10) and control (n = 10) groups, blood cortisol analysis and behavioural (time spent lying down, feeding, and standing) assessment pre and post-HT, and two days later. Resultantly, lower incidence rates of lameness and significantly higher time to first lameness event were recorded in the trimmed cows in grazing (27.4 cases/100/month, mean ± S.E; 8.12 ± 0.1) and non-grazing farms (31.9 cases/100/month, 8.05 ± 0.2) compared to the controls (48.4 and 45.8 cases/100/month). Likewise, the incidence rate of lameness was 28.7, 15.8 and 42.8 cases/100 cows/months in TRIM1, TRIM2 and CON respectively during lactation, with TRIM2 demonstrating a significantly higher time to first lameness event (8.26 ± 0.16) than CON (7.32 ± 0.2). Cortisol levels increased significantly (P < 0.05) in both groups after treatment compared to the basal levels. Hoof-trimmed cows spent significantly more time lying down, and less time standing and at the feed bunk compared to CON on day 1. The fifth study entailed a randomised clinical trial involving five groups of moderately lame cows (n = 81): Group A (therapeutic trim + administration of ketoprofen + hoof block), Group B (therapeutic trim + hoof block), Group C (therapeutic trim + ketoprofen), Group D (therapeutic trim only), and Group E (non-lame cows receiving only maintenance trim). The enrolled cows were observed weekly until day 28 after treatment. Group A had the highest recovery rate (75%; 15/20, P < 0.05) compared to Group D (40%; 6/15). Groups A and E spent lesser time lying down (P < 0.05) compared to other treatments. Time spent at feed bunk was highest in Group E (P < 0.05) and lowest (P < 0.05) in Groups C and D. Hence, treatment protocols for hoof horn lesions affected both the lameness recovery rate and short-term behaviours in moderately lame cows. The last study was a survey conducted among dairy farmers (n = 114) in Peninsular Malaysia. Lameness was ranked as the second most important health issue in Malaysian dairies. Farmers showed satisfactory knowledge about the impact of lameness on dairy cattle welfare and production but most of them (75.8%; 22/29) underestimated lameness and rarely implemented proper management strategies in their farms. Conclusively, the present high lameness prevalence in Malaysian dairy farms requires effective control strategies. The modified HT method employed in this study demonstrated the potential of reducing lameness incidence in grazing and non-grazing cows. However, the impacts of HT and related treatment protocols on welfare indicators need to be considered. These findings add to the body of knowledge regarding the importance of lameness and hoof lesions in Malaysian dairies, and the role of HT techniques in minimising the negative impact on dairy cattle.